Novel multicomponent alloys - Cantor, B; Audebert, F; Galano, M; Kim, K; Stone, I; Warren, P (2005)
A wide range of novel multicomponent amorphous alloys can be manufactured by rapid solidification processing. This paper describes different types of multicomponent alloys: chill cast equiatomic substituted fcc and fcc/bcc CrMnFeCoNiNbGeVTi alloys, melt spun equiatomic substituted amorphous and quasicrystalline TiZrHfFeCoNiCuAgAl alloys and melt spun quasicrystalline AlFeCrTiVNbTa alloys.